Substance use disorders and violent behaviour in patients with severe mental disorders: A prospective, multicentre study. (December 2020) - Cavalera, Cesare; Ferrari, Clarissa; Bianconi, Giorgio; Bulgari, Viola; Candini, Valentina; Carrà, Giuseppe; Clerici, Massimo; Conte, Giovanni; Cricelli, Marta; Ferla, Maria Teresa; Iozzino, Laura; Macis, Ambra; et al.
Objective: The relationship between alcohol and substance use and the risk of violence exhibited by patients with mental disorders is under-researched. This prospective cohort study aims to compare patients with severe mental disorders and with different substance use behaviors in terms of sociodemographic and clinical characteristics, hostility, impulsivity and aggressive behaviors. Furthermore, this study aims to assess differences in violent behaviors during a 1-year monitoring follow-up. Methods: A total of 378 participants with severe mental disorders from Italian residential facilities and from four Departments of Mental Health (244 outpatients and 134 residential patients) were enrolled. Participants were categorized as Persons with Current Substance Use, Persons with Former Substance Use and Persons with Non-Substance Use. All these patients underwent a complex multidimensional assessment, including the lifetime and current substance use; a subsample of outpatients was also assessed with a laboratory substance assay including the testing for specific substances. We assessed the differences among these three groups in hostility, impulsivity and aggressive behaviors. Results: The results of the close 1-year monitoring show a significantly higher risk of violence for patients with severe mental disorders Persons with Current Substance Use compared to Persons with Former Substance Use and Persons with Non-Substance Use. Persons with Current Substance Use showed significantly higher scores for irritability, negativism and verbal assault compared to Persons with Non-Substance Use. Persons with Former Substance Use showed significantly higher scores for lifetime history of aggressive behaviors compared with patients with Persons with Non-Substance Use. Conclusion: These findings suggest that patients with comorbid mental illness and substance use disorders should be referred for specific interventions to reduce aggressive behavior and ensure patient well-being and community safety.